The Influence of Video and Image Media on Students' Mathematics Learning Outcomes Reviewed From Learning Interest - Eko Soni Yulianto; Sumiharsono, Rudy; Wesa Atmaja, I Wayan (Jurnal Pendidikan Indonesia, 2024)
Students' low interest in learning has an impact on low learning outcomes. The aim of this research is to analyze the influence of the use of video media and image media on student learning outcomes in terms of student interest in learning; The influence of high student interest in learning and low student interest in learning on student learning outcomes and the interaction of the use of learning media and student interest in learning with student learning outcomes in terms of student interest in learning. The population in this study was 34 students. Data collection consists of interest questionnaire data and learning outcomes test data. Questionnaires are used to collect data about students' learning interests using video and image media, while tests are related to student learning outcomes through video and image learning media. Analysis of this research data used the two-way Anova technique. The results of the research show that there are differences in the influence between the use of video media and image media on student learning outcomes in terms of learning interest. Based on descriptive analysis, it can be seen that high student interest is better than low student interest on student learning outcomes. The implications of this research are can provide valuable insight into the importance of choosing learning media that suits students' interests.